Alternatif Kajian Hadis sebagai Penafsir Alquran secara Tekstual - Abdullah Karim (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2019)
Textual interpretation of the Qur'an is the best interpretation, as long as the histories used as interpreters can be justified. The validity of the hadith which is used as the interpreter of the Qur'an must meet the following criteria: a. The interpretation of the Koran with the Koran must come from the Messenger of Allah. own. b. The interpretation of the Qur'an with the hadith must be based on the shahīh narration. c. Regarding the history of asbāb an-nuzūl, you must use a history whose expressions expressly indicate the cause of descending verses. d. The validity of the history used as the interpreter of the Qur'an will be more accurate if you consider the proportionality, professionalism and contextuality of the said traditions.